ANALYSIS OF THE IMPLEMENTATION OF LAW IN EVERY LEVEL OF SOCIETY IN INDONESIA - Dany Try Hutama Hutabarat; Agus Salam; Ahmad Zuwandana; Chairanda Al Azmi; Chandra Ridho Wijaya; Darnita; Ira Tania; Lili Kahirina Azhari Lubis; Muhammad Aldi Prayuda Sitorus; Robiatul Adawiyah; Rizky Sinaga (Transpublika Publisher, 2022)
Social stratification is a system in the social order that divides individuals into social classes. Finally, the social class will differentiate both the level and the rights and obligations of each individual in the class. The basis and core of a social stratification system is that there is an imbalance in the acquisition of rights and obligations, as well as responsibilities, between each individual and group in a series of social systems. The purpose of this research is to examine how law is applied at every level of society in Indonesia. This article was written using a qualitative technique, and it is designed to provide theoretical and practical usefulness to the community. According to the discussion, a social stratification system is one in which there is a distinction between one class or groups in standardized classes. Furthermore, there is evidence that there is a disparity between class stratification and law enforcement in Indonesia. As a result, law enforcement should be carried out in line with the applicable laws that have been jointly agreed upon in order to avoid creating a new long-term problems.